2017
DOI: 10.1371/journal.pone.0173329
|View full text |Cite
|
Sign up to set email alerts
|

The role of platelet and endothelial GARP in thrombosis and hemostasis

Abstract: BackgroundGlycoprotein-A Repetitions Predominant protein (GARP or LRRC32) is present on among others human platelets and endothelial cells. Evidence for its involvement in thrombus formation was suggested by full knockout of GARP in zebrafish.ObjectivesTo evaluate the role of GARP in platelet physiology and in thrombus formation using platelet and endothelial conditional GARP knock out mice.MethodsPlatelet and endothelial specific GARP knockout mice were generated using the Cre-loxP recombination system. The f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 34 publications
(53 reference statements)
1
22
0
Order By: Relevance
“…Interestingly, a recent study observed no pups for CMV-cre/ GARP fl/fl mice and suggested an "embryonic lethal phenotype" (39). As neither embryos nor dead pups have been analyzed for defects of CMV-cre/GARP fl/fl mice/embryos, whether the two kinds of GARP KO mice have the same lethal defects need to be further determined by analyzing CMV-cre/GARP fl/fl mice.…”
Section: Garp Is Essential For Mouse Palatogenesismentioning
confidence: 99%
“…Interestingly, a recent study observed no pups for CMV-cre/ GARP fl/fl mice and suggested an "embryonic lethal phenotype" (39). As neither embryos nor dead pups have been analyzed for defects of CMV-cre/GARP fl/fl mice/embryos, whether the two kinds of GARP KO mice have the same lethal defects need to be further determined by analyzing CMV-cre/GARP fl/fl mice.…”
Section: Garp Is Essential For Mouse Palatogenesismentioning
confidence: 99%
“…Tregs are not the only cell population that experiences GARP-FoxP3 co-regulation; human and murine megakaryocytes and platelets constitutively express both FoxP3 and the surface GARP/LAP complex. Interestingly, upon activation, platelets upregulate both GARP and FoxP3: protease-activated receptor 4 activating peptide (PAR4-AP) increases surface GARP, while phorbol ester myristate acetate upregulates FoxP3 expression [ 15 , 35 , 36 ]. Although the simultaneous upregulation of GARP and FoxP3 needs to be demonstrated, these findings suggest that platelets are another subset of cellular entities where GARP and FoxP3 interdependence might occur.…”
Section: Garp: Gene and Protein Structurementioning
confidence: 99%
“…A second study, performed in a genetic mouse model where Lrrc32 is specifically knocked out from platelets and megakaryocytes, shows that GARP is not necessary for thrombus formation and clot retraction, which is also confirmed by our own unpublished observations. Interestingly this last study shows that ex vivo platelet activation triggers increase in GARP surface expression, indicating that GARP might play a role in activating platelets [ 35 ]. Using the same platelet-specific GARP knockout mouse model, we recently demonstrated that GARP enhances the activation of latent TGF-β released by platelets [ 24 ].…”
Section: Platelet Garpmentioning
confidence: 99%
“…In the study, cardiac troponin levels increased and reached a peak concentration of 0.46 ± 0.10 µg/L, meanwhile plasma vWF, GP IIb/IIIa, and GMP-140 increased in rabbits after massive area pulmonary thromboembolism, and the peak concentrations of plasma cardiac troponin with vWF, GP IIb/IIIa, GMP-140, were significantly positively correlated. The increased vWF indicates that platelet adhesion increased and the pulmonary vascular endothelium was impaired 10,11 , which activated platelets when exposed to blood vessels via vWF 12,19 and aggravated thrombosis and increased vWF 20,21 . GP IIb/IIIa is the main glycoprotein in the platelet membrane 22 and mediates platelet and fibrinogen combination, which can be activated by collagen, causing endothelial cell damage by pulmonary thromboembolism, hypoxia, and pulmonary hypertension 22 .…”
Section: ■ Discussionmentioning
confidence: 99%